Análise dos processos hidrológicos em modelo didático de microbacias - Rodrigues, Valdemir Antonio [UNESP] (My University, 2011)
The models for the simulation of precipitation are used in an instructive way in understanding the behavior of surface water and groundwater. The objective was to analyze the hydrological processes occurring in watersheds, through simulation of rainfall in environment with vegetation and without vegetation and, observe the differences between direct surface runoff (Qds) and base flow (Qbf). Simulations were made in two rain intensities: P1 and P2 and three times: t1, t2, and t3. The results of runoff with vegetation were low: P1 (0.02, 0.03, and 0.06) and P2 (1.00, 2.66 and 4.50) mm, in three times, while in the environment without grass were higher: P1 (2.32, 3.25, and 5.51), P2 (10.01, 16.02 and 20.02) mm, which can cause erosion and flooding. However the base flow in the environment with vegetation was favorable: P1 (2.61, 3.19, and 6.09) and P2 (7.95, 16.85 and 19.49) mm, which reflects increased infiltration and better regularity of flow in the forested watershed. The observations in the two watersheds allowed visualizing the hydrological processes and demonstrate the importance of vegetation in regulating the water processes, in maintaining the groundwater and reducing the processes of runoff and erosion.

Os modelos para a simulação de precipitação são utilizados de forma didática no entendimento do comportamento da água superficial e subterrânea. O objetivo foi analisar os processos hidrológicos que ocorrem em microbacias, através de simulação de chuvas em ambientes com vegetação e sem vegetação e, observar as diferenças entre escoamento superficial direto (Qds) e fluxo de base (Qbf). Foram feitas simulações em duas intensidades de chuva: P1 e P2 e três tempos: t1 , t2 , e t3 . Os resultados de escoamento superficial com vegetação foram baixos: P1 (0,02; 0,03; e 0,06) e P2 (1,00; 2,66 e 4,50) mm, nos três tempos; enquanto que no ambiente sem cobertura vegetal foram superiores: P1 (2,32; 3,25; e 5,51); P2 (10,01; 16,02 e 20,02) mm, o que pode causar erosão e alagamentos. Já o fluxo de base no ambiente com vegetação foi favorável em: P1 (2,61; 3,19; e 6,09) e P2 (7,95; 16,85 e 19,49) mm, o que reflete uma maior infiltração e melhor regularidade da vazão na microbacia florestada. As observações nas duas microbacias permitiram visualizar os processos hidrológicos e comprovar a importância da cobertura vegetal na regulação dos processos hídricos, na manutenção do lençol freático e na diminuição dos processos de escoamento superficial e erosão.
Analysis of hydrological processes in teaching model for watershed
Keywords: Rainfall simulation; Runoff surface; Base flow; Hydrologic processes; Simulação de chuva; Escoamento superficial; Fluxo de base; Processos hidrológico